1992
DOI: 10.2527/1992.7061928x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of white rot basidiomycetes on chemical composition and in vitro digestibility of oat straw and alfalfa stems

Abstract: Five white rot basidiomycetes were evaluated for their potential to improve ruminal degradation of oat straw and alfalfa stems. Phanerochaete chrysosporium (PC), Scytinostroma galactinum (SG), Phlebia tremellosa (PT), Phellinus pini (PP), and Pholiota mutabilis (PM) were incubated on oat straw and alfalfa stems for 30 d at 28 degrees C and 90% relative humidity. Detergent fiber and total fiber components (neutral sugars, uronic acids, Klason lignin [KL], and ester- and ether-linked non-core lignin phenolics), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 16 publications
(19 reference statements)
5
21
1
Order By: Relevance
“…The IVOMD ranged from 400 to 539 g/kg DM. The in vitro DM digestibility of oat straws (from 397 to 529 g/kg DM) was similar to the values reported by Lopez et al (2005) and higher than the values reported by Brown & Almodares (1976) and Jung et al (1992). Differences in the digestibility of straws from different varieties may be due, not only to the chemical composition (Dias-da-silva & Guedes, 1990) but also to stem, leaf and seed ratios (Bhargava et al, 1988).…”
Section: Resultssupporting
confidence: 69%
“…The IVOMD ranged from 400 to 539 g/kg DM. The in vitro DM digestibility of oat straws (from 397 to 529 g/kg DM) was similar to the values reported by Lopez et al (2005) and higher than the values reported by Brown & Almodares (1976) and Jung et al (1992). Differences in the digestibility of straws from different varieties may be due, not only to the chemical composition (Dias-da-silva & Guedes, 1990) but also to stem, leaf and seed ratios (Bhargava et al, 1988).…”
Section: Resultssupporting
confidence: 69%
“…Inhibition of IVDMD with fungal treatment has also been previously reported, but the mechanism of inhibition is not understood (Jung et al 1992;Karunanandaa and Varga 1996). One possible explanation may be due to the chitin remaining in rape straw after incubation with fungi.…”
Section: In Vitro Fermentation and Pepsin-cellulase Assay Of Fungal Imentioning
confidence: 94%
“…The loss of these components from the feed is not economically desirable because less biomass is available for animal feed. In an earlier study Phanerocheate chrysosporium, a common and widely studied fungus, degraded lignin but also caused a high loss in total organic matter (TOM) (Jung et al, 1992). To overcome this problem, selective ligninolysis needs to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…However, loss of total organic matter is very high during the degradation of lignocellulosics, which limits its practical use and necessitates looking towards selective ligninolytic organisms (Jung et al, 1992). Phlebia species are known selective lignin degraders (Arora and Gill, 2000) and thus may possess the potential capability for improvement of digestibility of agro-residues.…”
Section: Introductionmentioning
confidence: 99%